Conference: Women and the Environment, Zimbabwe - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Women and the Environment, Zimbabwe, August 1999' Most African women belong to the underside of history in cultures in which they have key rôles in the maintenance of the environment' is how the organisers of an international conference announce...